1993
DOI: 10.1128/jcm.31.8.1987-1995.1993
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of various repetitive DNA elements as genetic markers for strain differentiation and epidemiology of Mycobacterium tuberculosis

Abstract: Five different genetic elements have been found to be associated with genetic rearrangements in Mycobacterium tuberculosis complex strains. Of these elements, the insertion sequence IS6110 is presently the most frequently used genetic marker for strain differentiation ofM. tuberculosis. In the present study we compared five genetic elements for their potentials to differentiate a given cluster ofM. tuberculosis strains. Because of the presence of only a single copy of IS6110 or two IS6110 copies at the same ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
193
1
8

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 417 publications
(214 citation statements)
references
References 29 publications
12
193
1
8
Order By: Relevance
“…The absence of IS6110 copies in some of Indian M. tuberculosis strains, as observed by some earlier studies, was also evident in the present study. 27,28 The strengths of our study include a prospective analysis of cases of suspected GITB using strict inclusion and exclusion criteria using three primers, IS6110, MPB64, and Protein b, versus single or two primers used in previous studies. The present study has also made an attempt to use composite reference standard for the comparative evaluation of multiplex PCR instead of using only culture or histopathology as the gold standard.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of IS6110 copies in some of Indian M. tuberculosis strains, as observed by some earlier studies, was also evident in the present study. 27,28 The strengths of our study include a prospective analysis of cases of suspected GITB using strict inclusion and exclusion criteria using three primers, IS6110, MPB64, and Protein b, versus single or two primers used in previous studies. The present study has also made an attempt to use composite reference standard for the comparative evaluation of multiplex PCR instead of using only culture or histopathology as the gold standard.…”
Section: Discussionmentioning
confidence: 99%
“…The reason to choose IS1081 as amplification target in the study is that this insertion element is carried by all M. tuberculosis complex strains investigated, with stable 5-6 copies (Collins and Stephens 1991;van Soolingen et al 1992van Soolingen et al , 1993Dziadek et al 2001). IS6110 has high copy numbers in most M. tuberculosis strains and is used as target by many nucleic acid amplification assays; however, strains with low copies or lacking IS6110 completely have been identified (van Soolingen et al 1993;Flores et al 2010). Recently, an IS6110-related element in a strain of M. smegmatis was identified and it has 67% amino acid identity and 79% similarity (Coros et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…These studies, however, were mainly carried out in the West and rarely involved Asian strains. A study conducted by von Soolingen et al (1993) revealed that many M. tuberculosis strains from Asia harbour relatively fewer copies of IS6110, and that a strain which lacked IS6110-DNA was isolated from India. Albeit the occurrence of IS6110-deleted tuberculosis strain in Singapore has not been reported, we suspected that it could have occurred in sample #25250.…”
Section: Discussionmentioning
confidence: 99%